Endothelial RSPO3 controls vascular stability and pruning through non-canonical WNT/Ca2+/NFAT signaling - Scholz, Beate; Wojtarowicz, Jessica; Mogler, Carolin; Boutros, Michael; Augustin, Hellmut (Developmental cell, 2016)
The WNT signaling enhancer R-spondin3 (RSPO3) is prominently expressed in the vasculature. Correspondingly, embryonic lethality of Rspo3-deficient mice is caused by vessel remodeling defects. Yet the mechanisms underlying vascular RSPO3 function remain elusive. Inducible endothelial Rspo3 deletion (Rspo3-iECKO) resulted in perturbed developmental and tumor vascular remodeling. Endothelial cell apoptosis and vascular pruning led to reduced microvessel density in Rspo3-iECKO mice. Rspo3-iECKO mice strikingly phenocopied the non-canonical WNT signaling-induced vascular defects of mice deleted for the WNT secretion factor Evi/Wls. An endothelial screen for RSPO3 and EVI/WLS co-regulated genes identified Rnf213, Usp18, and Trim30α. RNF213 targets filamin A and NFAT1 for proteasomal degradation attenuating non-canonical WNT/Ca2+ signaling. Likewise, USP18 and TRIM5α inhibited NFAT1 activation. Consequently, NFAT protein levels were decreased in endothelial cells of Rspo3-iECKO mice and pharmacological NFAT inhibition phenocopied Rspo3-iECKO mice. The data identify endothelial RSPO3-driven non-canonical WNT/Ca2+/NFAT signaling as a critical maintenance pathway of the remodeling vasculature.
Gesehen am 12.02.2019